Pandangan Ibn âArabÃ® tentang al-Qurâan sebagai Penghimpun - Wahyudi, Chafid (Mutawatir, 2015)
The leaders and observers disagree about sufism narated by Ibn âArabÃ®. Some parties considered him as a sufi who does not rely on the Koran, but others actually had put him always associated with the Koran. Although Ibn âArabÃ® considered not to rely on the Koran, he claimed that the knowledge gained is through the âopeningâ or âdisclosureâ (fath, kashf) with respect to the actual meaning of the Koran. Ibn âArabÃ® wrote, We are not quoting the words of the philosopher at all, nor the words of others. What we argue in this book and all our other books are what is given through Kashf and dictated by al-Haqq. Based on this claim, the authors try to lift the view of Ibn âArabÃ® on the Koran